2021
DOI: 10.1111/trf.16558
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic hemolysis is a donor‐specific feature of red blood cells under various storage conditions and genetic backgrounds

Abstract: Background: Transfusion research has recently focused on the discovery of red blood cell (RBC) storage capacity biomarkers and the elucidation of donor variation effects. This shift of focus can further strengthen personalization of transfusion therapy, by revealing probable links between donor biology, RBC storage lesion profile, and posttransfusion performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Genome-wide association studies (GWAS) identified several loci associated with hemolysis (Page et al, 2021;Fang et al, 2022) or metabolism (Moore et al, 2022) of stored RBCs, and similar conclusions also arose from classic twin studies (van 't Erve et al, 2014a;van 't Erve et al, 2014b). Correlation analyses support these findings (Reisz et al, 2017;Tzounakas et al, 2021), and enrich them with inter-correlations, namely, correlations between distinct parameters, either before/during storage, or between different time points of storage (D'Alessandro et al, 2021;Thomas et al, 2021;Anastasiadi et al, 2022). Such information has the potential to indicate or hint at how variation in one parameter might affect another, and therefore, lead to a better understanding of the "dialogue" between discrete aspects of RBC life during storage.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Genome-wide association studies (GWAS) identified several loci associated with hemolysis (Page et al, 2021;Fang et al, 2022) or metabolism (Moore et al, 2022) of stored RBCs, and similar conclusions also arose from classic twin studies (van 't Erve et al, 2014a;van 't Erve et al, 2014b). Correlation analyses support these findings (Reisz et al, 2017;Tzounakas et al, 2021), and enrich them with inter-correlations, namely, correlations between distinct parameters, either before/during storage, or between different time points of storage (D'Alessandro et al, 2021;Thomas et al, 2021;Anastasiadi et al, 2022). Such information has the potential to indicate or hint at how variation in one parameter might affect another, and therefore, lead to a better understanding of the "dialogue" between discrete aspects of RBC life during storage.…”
Section: Introductionmentioning
confidence: 77%
“…The maintenance of proportional storage, osmotic and mechanical hemolysis levels, among all time points in every condition tested, suggests that hemolysis is more a function of donor features than of additive solution modifications. According to previous studies, the osmotic fragility of stored RBCs is strongly donor-dependent since it varies proportionally to the circulation levels ( Tzounakas et al, 2021 ), being moderately associated with genes implicated in RBC structure and volume ( Page et al, 2021 ). The undeniable contribution of structural proteins and ion channels to mechanical fragility ( Smith et al, 2018 ; Svetina et al, 2019 ), leads to the assumption that there is a corresponding donor effect.…”
Section: Discussionmentioning
confidence: 99%
“…29 Intriguingly, when HOD and KEL are expressed on the same cell the impact of antigenspecific storage outcomes was preserved, strongly suggesting that even with mixed sex donor RBCs, storage can differentially impact alloimmunization. However, strainspecific modifications of storage in addition to donor sex, which can likewise impact RBC storage, 19,30 may also impact antigen-specific storage outcomes. Despite these limitations, the ability of this system to model key features of RBC alloimmunization provides important insight into general principles of RBC storage that may shape the likelihood of alloimmunization.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, menopause seems to promote membrane remodeling of red cells, especially during prolonged storage [59]. Furthermore, osmotic fragility, an aspect that is very important for hemolysis during storage and after transfusion of stored blood, appears correlated with donor sex [81]. So far, comparable data for the impact of donor sex on the storage lesion in large animal red blood cells are poor.…”
Section: Discussionmentioning
confidence: 99%